Stability and regularization of partially integer problems of vector optimization with possible perturbations of criteria - Lebedeva , Т.Т.; Semenova, N.V.; Sergienko, T.I. (Reports of the National Academy of Sciences of Ukraine, 2022)
New results related to the study of stability and regularization of partially integer vector optimization problems with possible perturbations of the input data of a vector criterion consisting of quadratic or linear functions are presented. The stability of problems with quadratic criteria for the case of finding solutions that are optimal according to Slater is proved. For the Pareto optimization case, an approach to the regularization of partially integer problems with linear criterion functions is developed.